2021
DOI: 10.23960/ujet.v10.i2.202103
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between students’ reading habit and reading ability at the first grade of MAN 1 Bandar Lampung

Abstract: This quantitative research was aimed to find out whether there was any significant correlation between students’ reading habit and reading ability and also to find out the most correlated aspect of reading with students’ reading habit. The subject of research were thirty four students at MAN 1 Bandar Lampung. The researcher measured reading habit by using questionnaire. On other hand, reading test was used to assest students’ reading ability. The data from both instruments were analyzed by using Pearson Produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…Third, study conducted by Sartika et al (2020) which indicated that the relationship between students' reading habit and their reading comprehension existed, and the corelation was medium. Next, a study conducted by Rahayu et al (2021) showed that high and strong correlation as the result of this research. Then, study carried out by Darojat, et al (2020) which resulted that were found a very high and strong correlation between the variables.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Third, study conducted by Sartika et al (2020) which indicated that the relationship between students' reading habit and their reading comprehension existed, and the corelation was medium. Next, a study conducted by Rahayu et al (2021) showed that high and strong correlation as the result of this research. Then, study carried out by Darojat, et al (2020) which resulted that were found a very high and strong correlation between the variables.…”
Section: Introductionsupporting
confidence: 63%
“…Second, Erlina et al (2019) discovered in a research of English education undergraduate students that their reading habits correlated to their academic accomplishment. Then, Rahayu et al (2021) discovered that there was a significant relationship between their reading habit and reading comprehension in tenth grade learners.…”
Section: Discussionmentioning
confidence: 99%